2022
DOI: 10.3390/cells11172738
|View full text |Cite
|
Sign up to set email alerts
|

Small Nucleolar RNAs in Pseudoexfoliation Glaucoma

Abstract: Small nucleolar RNAs (snoRNAs) are small non-coding regulatory RNAs that have been investigated extensively in recent years. However, the relationship between snoRNA and glaucoma is still unknown. This study aims to analyze the levels of snoRNA expression in the aqueous humor (AH) of patients with pseudoexfoliation glaucoma (PEXG) compared to a control group and identify hypothetical snoRNA-dependent mechanisms contributing to PEXG. The AH was obtained from eighteen Caucasian patients, comprising nine PEXG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Temperature adaptability is a complex trait regulated by multiple genes (Goyal et al, 2016). Numerous core genes involved in biological require other assistance for transport between cells (Gasinska et al, 2022). Using the CRISPR/Cas9 system to knock out PxGCC2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature adaptability is a complex trait regulated by multiple genes (Goyal et al, 2016). Numerous core genes involved in biological require other assistance for transport between cells (Gasinska et al, 2022). Using the CRISPR/Cas9 system to knock out PxGCC2…”
Section: Discussionmentioning
confidence: 99%
“…They were not transmembrane proteins. Therefore, they may require other assistance for transport between cells (Gasinska et al, 2022). Using the CRISPR/Cas9 system to knock out PxGCC2 and PxKPNB1 , we found that the deletion of PxGCC2 and PxKPNB1 reduced the ability of P. xylostella to respond to temperature extremes, particularly in terms of population dynamics.…”
Section: Discussionmentioning
confidence: 99%